Ending risk-group HBV vaccination for MSM after the introduction of universal infant HBV vaccination: A mathematical modelling study. Issue 21 (18th May 2021) - Xiridou, Maria; Visser, Maartje; Urbanus, Anouk; Matser, Amy; van Benthem, Birgit; Veldhuijzen, Irene
Highlights: Risk-group HBV vaccination for MSM has led to major reductions in HBV transmission. Universal HBV vaccination can result in further decline in HBV incidence among MSM. Early termination of risk-group vaccination would lead to less averted infections. The PrEP program may lead to more HBV vaccinations and less HBV infections in MSM. High rates of HBV vaccination, testing, and treatment needed to control HBV in MSM. Abstract: Background: Risk-group HBV vaccination for men who have sex with men (MSM) was introduced in the Netherlands in 2002, followed by universal infant vaccination in 2011, that will enable termination of risk-group vaccination over time. The introduction of pre-exposure prophylaxis (PrEP) for HIV prevention might result in increased HBV testing and vaccination against HBV. The aim of this study was to investigate the impact of the transition from risk-group to universal HBV vaccination, accounting for improvements in HBV testing and treatment, as well as the introduction of PrEP. Methods: We developed a mathematical model for HBV transmission among MSM. Universal vaccination was modelled by assigning some MSM (5–15% in 2028 increasing to 80–90% in 2033 and thereafter) to be vaccinated when they become sexually active. We investigated different scenarios assuming 0.5% extra vaccination rate and 0.5% extra testing rate due to PrEP consultations; and 5% of HIV-negative MSM on PrEP, that will reduce the probability of HBV acquisition by 88%. Results: Universal vaccination resulted in a reduction of 24% (interquartile range; 22–25%) of the total number of HBV infections among MSM estimated to occur from 2020 to 2070. With universal vaccination, terminating risk-group vaccination in 2030 or 2040 resulted in 30% or 10% more HBV infections over 2020–2070, respectively, compared to continuation of risk-group vaccination until 2070. With PrEP and continued risk-group vaccination, the total number of HBV infections over 2020–2070 was reduced by 13%. Conclusions: Universal HBV vaccination can lead to a major reduction in HBV incidence among MSM in the future. The reduction becomes smaller when ending risk-group HBV vaccination, but larger by PrEP use for HIV prevention. Efforts to keep high levels of HBV vaccination, testing, and treatment have to be continued in the coming decades in order to eliminate HBV as a health threat for MSM.